Experimental approaches to evaluate activities of cytochromes P450 3A - Bořek-Dohalská, Lucie; Hodek, Petr; Hudeček, Jiří; Stiborová, Marie (Interdisciplinary toxicology, 2008)
Cytochrome P450 (CYP) is a heme protein oxidizing various xenobiotics, as well as endogenous substrates. Understanding which CYP enzymes are involved in metabolic activation and/or detoxication of different compounds is important in the assessment of an individual's susceptibility to the toxic action of these substances. Therefore, investigation which of several in vitro experimental models are appropriate to mimic metabolism of xenobiotics in organisms is the major challenge for research of many laboratories. The aim of this study was to evaluate the efficiency of different in vitro systems containing individual enzymes of the mixed-function monooxygenase system to oxidize two model substrates of CYP3A enzymes, exogenous and endogenous compounds, α-naphtoflavone (α-NF) and testosterone, respectively. Several different enzymatic systems containing CYP3A enzymes were utilized in the study: (i) human hepatic microsomes rich in CYP3A4, (ii) hepatic microsomes of rabbits treated with a CYP3A6 inducer, rifampicine, (iii) microsomes of Baculovirus transfected insect cells containing recombinant human CYP3A4 and NADPH:CYP reductase with or without cytochrome b(5) (Supersomes™), (iv) membranes isolated from of Escherichia coli, containing recombinant human CYP3A4 and cytochrome b(5), and (v) purified human CYP3A4 or rabbit CYP3A6 reconstituted with NADPH:CYP reductase with or without cytochrome b(5) in liposomes. The most efficient systems oxidizing both compounds were Supersomes™ containing human CYP3A4 and cytochrome b(5). The results presented in this study demonstrate the suitability of the supersomal CYP3A4 systems for studies investigating oxidation of testosterone and α-NF in vitro.
Keywords: α-naphthoflavone; metabolism; cytochrome P450 3A